Existence of SARS-Cov-2 in the Peritoneal Fluid - Ilgen, Orkun; Ozgozen, Mehmet Eyuphan; Appak, Ozgur; Ertan, Begum; Tımur, Hikmet Tunc; Dogan, Omer Erbil; Posacı, Cemal (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To determine the existence of SARS-CoV-2 in the peritoneal fluid to assess the risk of exposure through surgical smoke and aerosolization threatening healthcare workers during abdominal surgery.Background SARS-CoV-2 is a respiratory virus and possible ways of viral transmission are respiratory droplets, close contact, and fecal-oral route. Surgeries pose risk for healthcare workers due to the close contact with patients. Aerosolized particles may be inhaled via the leaked CO2 during laparoscopic procedures and surgical smoke produced by electrocautery.Methods All the data of 8 patients, who were tested positive for COVID–19, were collected between August 31, 2020 and April 30, 2021. Recorded clinicopathologic data included age, symptoms, radiological and laboratory findings, antiviral treatment before surgery, type of surgery and existence of the virus in the peritoneal fluid. Nasopharyngeal swab RT-PCR was used for the diagnosis. COVID–19 existence in the peritoneal fluid was determined by RT-PCR test as well.Results All 8 COVID–19 positive patients were pregnant, and surgeries were cesarean sections. 1 of the 8 patients was febrile during surgery. Also only 1 patient had pulmonary radiological findings specifically indicating COVID-19 infection. Laboratory findings were as follows: 4 of 8 had lymphopenia and all had elevated D-dimer levels. Peritoneal and amniotic fluid samples of all patients were negative for SARS-CoV-2.Conclusion SARS-CoV-2 exposure due to aerosolization or surgical fumes does not seem to be likely, provided the necessary precautions are taken.
Keywords: SARS-CoV-2; peritoneal fluid; surgical smoke; amniotic fluid; COVID-19